APLIKASI MANAJEMEN BERBASIS SEKOLAH MELALUI PROGRAM GERAKAN SEKOLAH MENYENANGKAN (GSM) DI MADRASAH IBTIDAIYAH AL-HUSNA PONDOK AREN TANGERANG SELATAN - Ahmad Masruri (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This article aims toreveal the application of school-based management through the gera program of fun schools because from the kebanyof schools in South Tangerang only a few schools implement management system programs like this . The research method used is qualitative with a descriptive method. This article focuses on the school movement program which is part of school-based management which is carried out at the Ibtidaiyyah Al-Husna Pondok Aren Madrasah, South Tangerang. The Fun School Movement program can improve the quality of learning obtained by children. Among them, by starting icebreaking before the activity starts, there are rewards as an encouragement for children's learning, making creativity such as zones (presence, agreement, emotions, etc.). Theprogram implemented by schools based on the fun school movement is very relevant to thenational law system. Education is a child's conscious effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual, religious, self-control, personality, intelligence, noble character and the necessary skills of themselves, society, nation, and state.